TENTATIVA DE LOS ENIGMAS (WALTER BENJAMIN HABLA DE KAFKA) - Contreras Castro, Fernando (2023)
Based on Walter Benjamin’s essay “Franz Kafka: On the Tenth Anniversary of His Death”, the author discusses how Benjamin encounters in Kafka a configuration of power which is marked by the paradox of the simultaneous permanency in and expulsion from Paradise, the absolution and the condemnation of original sin, which overwehlms both the powerful and the oppressed.